Application of a New Integrated Bipolar and Ultrasonic Energy Device in Laparoscopic Hysterectomies. (13th February 2013) - Lin, Harvard Z.; Ng, Y. W.; Agarwal, A.; Fong, Y. F.
Abstract : Objective . A retrospective study to evaluate the Thunderbeat, a new vessel sealing device in a small group of patients undergoing laparoscopic hysterectomy to test the safety and effectiveness in achieving hemostasis. Method . The Thunderbeat was used in 12 cases of total laparoscopic hysterectomy. Operative performance involving hemostasis, sealing/coagulation, cutting, dissection, and tissue manipulation was evaluated. Results . No complications were encountered intraoperatively and postoperatively. Intraoperative experience involving hemostasis, sealing/coagulation, and cutting was optimal. Tissue handling was acceptable except for fine dissection. Conclusion . The Thunderbeat is an efficient and safe alternative to standard bipolar in laparoscopic hysterectomy. Larger studies are required to evaluate the cost-effectiveness and significant reduction in operating times as compared to conventional bipolar energy.